The association between polymorphisms in the CYP17 and 5alpha-reductase (SRD5A2) genes and serum androgen concentrations in men. - Allen, N; Forrest, MS; Key, T (2001)
Prospective studies suggest that prostate cancer risk may be increased in association with high serum concentrations of free testosterone and androstanediol glucuronide (A-diol-g). Polymorphisms have been identified in the 17-hydroxylase cytochrome P450 gene (CYP17) and the steroid 5alpha-reductase type II gene (SRD5A2), two genes that are involved in the biosynthesis and metabolism of androgens in men. The CYP17 MspA1 I polymorphism has been associated with increased prostate cancer risk, and the SRD5A2 V89L polymorphism has been associated with low A-diol-g in Asian men, a serum marker of 5alpha-reductase activity. The purpose of this study was to investigate the association between these two polymorphisms and serum sex hormone concentrations in 621 British men. In particular, we wanted to test the hypotheses that the A2 allele in the CYP17 gene is associated with increased serum testosterone concentrations, and the L allele in the SRD5A2 gene is associated with reduced A-diol-g concentrations. Mean hormone concentrations were evaluated in each genotype and adjusted for age and other relevant factors. We found no evidence that the CYP17 MspA1 I polymorphism was associated with higher testosterone levels. The L/L genotype of the SRD5A2 V89L polymorphism was associated with a 10% lower A-diol-g concentration, but this was not significant at the 5% level. However, the L/L genotype of the V89L polymorphism was associated with significantly lower concentrations of testosterone and free testosterone (by 12% and 16%, respectively) and an 8% higher sex hormone-binding globulin concentration. These results suggest that the CYP17 MspA1 I polymorphism is not associated with testosterone concentrations and that the SRD5A2 V89L polymorphism is not a strong determinant of A-diol-g concentration in Caucasian men.